Dobbing: Australia's favourite emergency pastime. (March 2022) - Bond, Catherine
While 'dobbing' is arguably viewed negatively, this behaviour has been on the rise during the COVID-19 pandemic. Drawing on examples from the First World War and the pandemic, this article argues that this increased activity is typical of the Australian community during emergencies, facilitated by extensive legal frameworks that encourage this type of reporting.